Characterisation of lignocellulosic sugars from municipal solid waste residue. - Meor Hussin, Anis Shobirin; Collins, Samuel R. A.; Merali, Zara; Parker, Mary L.; Elliston, Adam; Wellner, Nikolaus; Waldron, Keith W. (Elsevier, 2013)
Municipal solid waste (MSW) contains significant quantities of plant-derived carbohydrates which have the potential to be exploited as a biomass source. This study evaluated the chemical composition and fractionation of MSW water-insoluble organic matter remaining after recycling of other components (MSWR). The organic matter was prepared as a dry, alcohol insoluble residue (MSWR-AIR, comprising w = 6% of original MSW) and size fractionated into fractions A, B, C & D. Carbohydrates were present in all the sub-fractions, comprising up to w = 54%; their complexity was also assessed by FT-IR spectroscopy. The lignin content in the samples ranged from w = 11–22%. The most carbohydrate-rich subfraction (C; w = 4% original MSW) was sequentially extracted to provide information on the likely constituent cell wall-derived polymers, sugar compositions and uronic acid content. The results indicate that approximately w = 25% of the MSWR-AIR comprises glucose, which appears to be mostly cellulosic in origin. The results are discussed in relation to the potential for exploitation.